Genetic characterization of herbicide resistance and investigation of physiological basis of herbicide efficacy under temperature stress in grain sorghum (Sorghum bicolor (L.) Moench) - Parrey, Yasir Nazir (My University, 2025)
Grain sorghum (Sorghum bicolor (L.) Moench) is a multipurpose crop valued for food, feed, and fuel. Post-emergence (POST) herbicide applications are essential for effective weed control in grain sorghum to improve yields. Hydroxyphenyl pyruvate dioxygenase (HPPD) inhibitors (e.g., mesotrione and tembotrione) are widely used to control a broad spectrum of weeds. While HPPD-inhibiting herbicides are effective in corn (Zea mays L.) and wheat (Triticum aestivum L.), their use in sorghum is restricted due to crop injury. Previous research identified and characterized HPPD-inhibitor resistant genotypes of sorghum. Rising global temperatures due to climate change and climate variability can alter herbicide efficacy and increase crop sensitivity to herbicide injury. Although the crop responses to herbicides under high-temperature (HT) stress have been reported, the physiological mechanisms underlying such responses remain poorly understood. The objectives of this thesis were to: 1) evaluate and characterize HPPD-resistant sorghum parental lines and their F₁ progeny for resistance to mesotrione and tembotrione; 2) evaluate the physiological basis of sorghum injury to HPPD-inhibitors (e.g., mesotrione) and synthetic auxinic herbicides (e.g. 2,4-D) under optimum (OT) and HT conditions. Experiments were conducted either in the greenhouse or in controlled environmental growth chambers. For Objective 1, mesotrione-resistant (G-10) and tembotrione-resistant (G-200, G-350) sorghum genotypes, along with the susceptible line S-1, were evaluated in the greenhouse. F₁ hybrids were produced via reciprocal crosses using the two resistant lines and various genotypes as parental lines. Mesotrione (0–8x; 1x = 105 g ai ha⁻¹) and tembotrione (0–4x; 1x = 92 g ai ha⁻¹) were applied on parental and hybrid progeny at the 4–5 leaf stage. G-10 and its F₁ hybrid with G-200 (G-200 × G-10) showed significantly higher mesotrione resistance, exhibiting 8.8-fold and 11.2-fold greater resistance, respectively, compared to the sensitive genotype S-1. Visual injury scores and SPAD readings (chlorophyll index) confirmed better recovery and chlorophyll retention in resistant lines, supporting their use in breeding mesotrione-resistant cultivars. The genotype G-200 and its hybrid with G-10 (G-10 x G-200) exhibited the highest resistance to tembotrione, showing 3.42-fold and 3.55-fold greater resistance, respectively, compared to the susceptible control. This was followed by G-350, which showed 2.42-fold greater resistance and also demonstrated higher biomass and chlorophyll content than the susceptible lines. Other genotypes and hybrids showed intermediate resistance. Overall, F₁ hybrids G-200 x G-10 and G-10 x G-200 exhibited the highest resistance to mesotrione and tembotrione, respectively, suggesting additive effects and potential for stacking resistance in sorghum breeding programs. For objective 2, sorghum genotypes RTx430 and P84G62 were grown under two temperature regimes: OT: (32/22°C day/night) and HT: (40/30°C day/night). A mixture of radiolabeled [¹⁴C]- and unlabeled mesotrione or 2,4-D was applied to the fourth youngest leaf, and foliar uptake and translocation were assessed at 6 and 24 hours after treatment (HAT). A malathion (a known inhibitor of cytochrome P450 enzyme activity) pre-treatment assay was also used to evaluate the role of cytochrome P450 enzymes in herbicide detoxification under temperature stress. Results indicate that herbicide uptake increased under HT for both herbicides, however, most of the absorbed radioactivity for mesotrione remained in the treated leaf at HT, likely due to reduced metabolism, leading to greater injury. In contrast, under OT, a greater portion of the absorbed radioactive 2,4-D remained in the treated leaf, likely due to reduced metabolism associated with lower cytochrome P450 (CYP) activity, resulting in increased injury. The results of objective 1, provides a foundation for developing herbicide-resistant sorghum hybrids via introgression, which can help effective, POST weed management; and results from objective 2 suggests that temperature stress alters herbicide metabolism and distribution differently depending on the herbicide. Under HT, reduced translocation of mesotrione likely due to impaired metabolism led to greater injury, whereas under OT, reduced translocation of 2,4-D from the treated leaf potentially due to lower cytochrome P450 (CYP) activity and metabolism also resulted in increased injury. Overall, the results of this research will help in effective weed management in grain sorghum.
Keywords: Sorghum; Herbicide resistance; Herbicide efficacy; Temperature stress; Physiology